Kendali LQR pada sistem transmisi data dengan sumber jaringan jamak - Dita Anies Munawwaroh (Universitas PGRI Semarang, 2021)
In this study, we discussed about controlling data transmission system with multi-source networks. The control technique used in this research is quadratic linear regulator with discrete time. Quadratic linear regulator is optimal control with objective function in the quadratic form and has linear constraint. The control technique is used to optimize data transmission rate. Assumed, the data will be received 100 %, although the data transmission process has delayed time. From the stability analysis and the properties, the rule of control will make it optimum and asymptotic stable.